2017
DOI: 10.18632/oncotarget.15376
|View full text |Cite
|
Sign up to set email alerts
|

Reappraisal of XRCC1 Arg194Trp polymorphism and glioma risk: a cumulative meta-analysis

Abstract: The association between XRCC1 Arg194Trp polymorphism and glioma risk were inconsistent from published meta-analyses and epidemiological studies. Hence, we performed this updated and cumulative meta-analysis to reappraisal this relationship. PubMed, Embase, CBM (Chinese Biomedical Database), and CNKI (China National Knowledge Internet) databases were comprehensively searched up to August 13, 2016 (updated on December 22, 2016). After study selection and data extraction from eligible studies, the association was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Custodio et al [20] reported an increased risk for gliomas in Caucasians with the XRCC1 rs1799782 SNP (Brazilian population), but they also observed improved survival in the presence of the 194Trp allele. Finally, in the study published by Fan et al [8] there was an increased risk for gliomas in participants that had TT or CT + TT genotypes (Table 2) [14][15][16][17][18][19][20][21][22][23][24].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Custodio et al [20] reported an increased risk for gliomas in Caucasians with the XRCC1 rs1799782 SNP (Brazilian population), but they also observed improved survival in the presence of the 194Trp allele. Finally, in the study published by Fan et al [8] there was an increased risk for gliomas in participants that had TT or CT + TT genotypes (Table 2) [14][15][16][17][18][19][20][21][22][23][24].…”
Section: Resultsmentioning
confidence: 99%
“…Lu et al [24] reviewed sixteen published papers and reported increased risk only for Asians with TT and TT + CT genotype in their meta-analysis. Xu et al [25] found an increased risk only in Asians with CT + TT genotype and in both Asians and Caucasians with TT genotype.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, glioma accounts for about 50% of primary tumors of the central nervous system (4,5). Epidemiology studies have indicated that genetic factor is an established risk factor for brain cancer patients (6,7). Furthermore, external environment, such as long-term mobile phone use (8) could increase the risk of glioma.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has shown that polymorphisms in DNA repair genes could influence individual DNA repair capacity [4]. Lu et al suggested that XRCC1 Arg194Trp polymorphism was associated with increased risk for glioma, especially in Asians [5]. Yang et al indicated that no association between rs25487 or rs1799782 gene polymorphism and risk of female reproductive cancer risk was found [6].…”
Section: Introductionmentioning
confidence: 99%